2009
DOI: 10.1021/ef8007486
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Changes of Main Compositions and Extractives of Rice Straw Pretreated with Sodium Hydroxide for Biogas Production

Abstract: This study was conducted to investigate the changes of main compositions and extractives and their effects on biogas yield enhancement. Four NaOH doses (4%, 6%, 8%, and 10%) and four loading rates (35, 50, 65, and 80 g/L) were used. The rice straw was first pretreated by NaOH in solid-state conditions and anaerobically digested. The main compositions and extractives were then analyzed. The results showed that, compared to the untreated rice straw, 3.2%−58.1% more biogas yields were obtained with 4%−10% NaOH-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 34 publications
7
28
0
Order By: Relevance
“…2009 [98] Studied the influence of different operating condition and method on the production of biogas using rice straw through anaerobic digestion.…”
Section: [93]mentioning
confidence: 99%
“…2009 [98] Studied the influence of different operating condition and method on the production of biogas using rice straw through anaerobic digestion.…”
Section: [93]mentioning
confidence: 99%
“…In comparison with other pre-treatments with mineral acids [14,15] or bases [16,17] added to the reaction media, autohydrolisis has a lower environmental impact, as the only reagent is water and no further detoxification treatments are required to neutralize the sludges. Autohydrolysis is also a cost effective process, as the variation of pH in the liquors is very low and there is no corrosion of the equipment [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Corn stover had been ground to 5-10-mm particles, but it is not clear whether pretreated biomass was rinsed prior to digestion. Similarly, He et al [40] found that optimal conditions for rice straw were 6% NaOH (wt/wt) for 3 weeks at 20 • C (68 • F). They reported a particle size of 5-10 mm and did not rinse biomass prior to digestion.…”
Section: Discussionmentioning
confidence: 92%